Cadmium and lead tolerant bacteria isolated from industrial waste water (Dhaka University Journal of Biological Sciences, 2017)
An in vitro study was conducted to isolate, identify and characterize heavy metal resistant bacteria from industrial waste water and to determine their tolerance capacity to cadmium and lead. Different morphological, physiological and biochemical tests were carried out to identify the bacterial isolates in the waste water. A total of eight bacterial isolates viz., Staphyllococcus intermedius, Pseudomonas aeruginosa, Bacillus cereus, Bacillus subtilis, Escherichia coli, Acinetobacter baumanii, Pseudomonas flavescens and Acinetobacter lwofii were identified from metal polluted tannery and steel industrial areas. Bacterial response to cadmium tolerance was determined by treating them with CdCl2 solution at a rate of 1, 2, 2.5 and 5 μg/ml. In case of lead tolerant bacteria, PbCl2 solution was applied at a rate of 0.05, 0.125, 0.2 and 0.5 μg/ml. Pseudomonas aeruginosa isolated from waste water of steel industries and Bacillus cereus from tannery area was found to be the most tolerant species to the different doses of cadmium and lead. The study indicated that Pseudomonas aeruginosa and Bacillus cereus could be good candidates for the treatment and elimination of heavy metals from industrial waste water. The present study may be helpful to the bioremediation of heavy metals in the contaminated environment.Dhaka Univ. J. Biol. Sci. 26(1): 29-38, 2017 (January)